2016
DOI: 10.1074/jbc.m115.697045
|View full text |Cite
|
Sign up to set email alerts
|

Actin-Sorting Nexin 27 (SNX27)-Retromer Complex Mediates Rapid Parathyroid Hormone Receptor Recycling

Abstract: The G protein-coupled parathyroid hormone receptor (PTHR) regulates mineral-ion homeostasis and bone remodeling. Upon parathyroid hormone (PTH) stimulation, the PTHR internalizes into early endosomes and subsequently traffics to the retromer complex, a sorting platform on early endosomes that promotes recycling of surface receptors. The C terminus of the PTHR contains a type I PDZ ligand that binds PDZ domaincontaining proteins. Mass spectrometry identified sorting nexin 27 (SNX27) in isolated endosomes as a P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 89 publications
1
49
0
Order By: Relevance
“…This PDZ ligand assumes a Type I consensus sequence (E-T-V-M) that is compatible with the canonical recognition signature of the SNX27-PDZ domain. Parallel studies recently confirmed this engagement, thereby providing a direct molecular link to the ASRT complex [50, 63]. First, a PDZ-dependent interaction was demonstrated between PTHR and SNX27 by combining coimmunoprecipitation studies in HEK293 cells with isothermal titration calorimetry (ITC), the later titrating a series of native and mutant PTHR-PDZ-ligand peptides against the SNX27-PDZ domain.…”
Section: Asrt-mediated Endosome-to-plasma Membrane Recyclingmentioning
confidence: 95%
“…This PDZ ligand assumes a Type I consensus sequence (E-T-V-M) that is compatible with the canonical recognition signature of the SNX27-PDZ domain. Parallel studies recently confirmed this engagement, thereby providing a direct molecular link to the ASRT complex [50, 63]. First, a PDZ-dependent interaction was demonstrated between PTHR and SNX27 by combining coimmunoprecipitation studies in HEK293 cells with isothermal titration calorimetry (ITC), the later titrating a series of native and mutant PTHR-PDZ-ligand peptides against the SNX27-PDZ domain.…”
Section: Asrt-mediated Endosome-to-plasma Membrane Recyclingmentioning
confidence: 95%
“…SNX27 is directly bound to the retromer subunit VPS26 and simultaneously binds to a multitude of PDZ-and tyrosine-based sorting motifs in the cytosolic tail of its cargo proteins, thereby driving their recycling back to the cell surface (Steinberg et al, 2013;Gallon et al, 2014;Ghai et al, 2013). Retromer and SNX27 have been shown to recycle a wide range of surface molecules, ranging from signalling receptors like the β2-adrenergic receptor (Lauffer et al, 2010) or the parathyroid hormone receptor (PTHR) (Chan et al, 2016;McGarvey et al, 2016), and nutrient transporters (Steinberg et al, 2013) to neuronal glutamate receptors (Wang et al, 2013;Loo et al, 2014;Hussain et al, 2014). Although loss of retromer as well as of the WASH complex is lethal early in embryogenesis (Wen et al, 2011;Gomez et al, 2012), loss of SNX27 is lethal shortly upon birth of genetically modified mice (Cai et al, 2011), highlighting the physiological relevance of SNX27-, retromer-and/or WASH-driven recycling processes.…”
Section: Introductionmentioning
confidence: 99%
“…Can other proteins also contribute to the synergistic action of the β 2 AR on endosomal cAMP signaling mediated by PTH? For example, sorting nexin 27 (Snx27) regulating β 2 AR and PTHR recycling 1,23,24 might be sequestered by activated β 2 AR, thus allowing extended endosomal PTHR signaling. Does the mechanism shown in this study apply to other bone cells such as chondrocytes and osteocytes, which also express these two receptors?…”
mentioning
confidence: 99%